O treinamento de força associado à tarefa cognitiva melhora o balanço oxidativo, perfil inflamatório, capacidade cognitiva e função física de idosos institucionalizados - Araújo, Erivaldo Machado (2024)
Introduction: Population aging, coupled with increased life expectancy, has contributed to the growth of age-related diseases, resulting in physical and cognitive decline in older adults. This phenomenon is associated with a variety of negative health consequences, such as inability to perform daily tasks, falls and dementia. Oxidative stress and chronic inflammation are key factors in age-related diseases. While strength training is recognized as beneficial in combating these conditions, one intervention model that is gaining prominence is dual-task exercise, which simultaneously integrates motor and cognitive tasks. However, there are still few studies exploring the effectiveness of dual-task strength training in institutionalized older adults. Furthermore, the possible interaction between muscular strength, physical function, cognitive ability, clinical parameters and markers of oxidative stress and chronic inflammation in institutionalized older adults needs to be investigated. Finally, the effects of detraining in this population still need to be investigated. Objective: to investigate the effects of dual-task strength training and detraining on physical function, cognitive capacity, clinical parameters, oxidative stress markers and chronic inflammation in institutionalized older adults. Materials and Methods: 11 older adults (6 women, 5 men) with an average age of 83.0±8.1 were recruited through direct contact. This study was carried out over 41 weeks. Assessments (physical function, cognitive ability, clinical parameters, markers of oxidative stress and chronic inflammation) took place at weeks 1, 14, 28 and 41. Weeks 2 to 13 were used as a control period (routine activities), while the strength training protocol associated with the cognitive task took place from week 16 to week 27. From week 29 to week 40 was the detraining period. The dependent variables were collected before and after control, training and detraining. These were: physical function through performance on the Short Physical Performance Battery (SPPB); cognitive capacity through (i) the Mini-Mental State Examination (MMSE), (ii) the Clock Drawing Test (CDT) and (iii) the verbal fluency test; clinical parameters through analysis of the lipid profile, renal function and glycemia; muscular strength; oxidative stress through catalase (CAT), nitric oxide (NO) and TBARS and; inflammatory profile through IL-10 and TNF-α. The training program took place between weeks 16 and 27, twice a week with the following exercises: chair squats (standing and sitting); unilateral knee extension; unilateral hip flexion; plantar flexion and dorsiflexion. The cognitive task took place concurrently in the first two exercises, in which the older adults were asked to speak the names of animals, colors and fruits with each concentric action. The intensity and volume increased progressively over the weeks. Results: After dual-task strength training, an improvement was found in the CDT (p=0.049) and the MMSE (p=0.044) compared to the pre-control. Verbal fluency also increased significantly post-training compared to pre-control (p=0.004) and postcontrol (p=0.015). Post-training, verbal fluency -animals- improved compared to precontrol (p=0.024) and post-control (p=0.003). For physical function, there was an increase in balance post-training compared to pre-control (p=0.027). There was an improvement in walking speed post-training compared to pre-control (p=0.027) and also an increase in sitting and standing strength both post-training (p=0.008) and post-training (p=0.015) compared to pre-control. There was also an improvement in muscular strength post-training compared to pre-control (p<0.001 for all) and post-control (chair squat: p<0.001; unilateral knee extension: p=0.012; unilateral hip flexion: p<0.001; unilateral plantar flexion and dorsiflexion: p<0.001). This improvement was maintained posttraining in unilateral knee extension (p=0.009). In oxidative stress, it was found: a decrease in TBARS post-training compared to pre-control (p=0.003) and post-control (p=0.007); an increase in NO post-training compared to pre-control (p=0.025) and postcontrol (p=0.018) and; an improvement in redox balance both post-training and posttraining when compared to pre- and post-control (p<0.001 for all). Finally, in the inflammatory profile, IL-10 increased significantly post-training compared to pre-control (p=0.008) and post-control (p=0.035). In addition, TNF-α decreased post-training compared to post-control (p=0.006) and there was a significant improvement in the IL10/TNF-α ratio in the post-training period compared to the pre-control (p=0.009) and post-control (p=0.004) periods. Conclusion: Dual-task strength training provided improvements in physical function, cognitive capacity, muscular strength, markers of oxidative stress and chronic inflammation in institutionalized older adults. In addition, these effects of dual-task strength training improved physical function, cognitive ability, muscular strength, oxidative stress and chronic inflammation are maintained after a period of detraining. Dual-task strength training can be a strategy to prevent and improve different capacities in institutionalized older adults. In addition, it is a strategy that can reduce public spending on health. Finally, public policies involved in health promotion for the elderly, especially Older adults living in long-term care facilities, can benefit from the prescription of a dual-task strength training program for a better quality of life.